2006
DOI: 10.1038/sj.jp.7211560
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complications of pregnancy increase beyond 40 weeks of gestation in low-risk women

Abstract: Objective: We sought to determine when rates of maternal pregnancy complications increase for low-risk nulliparous and multiparous women at term. Methods:We designed a retrospective cohort study of low-risk women delivered beyond 37 weeks gestational age from 1976 to 2001. Rates of mode of delivery and maternal complications of labor and delivery were examined by gestational age with both bivariate and multivariate analyses. Statistical significance was designated by P<0.05.Results: We found that among the 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 20 publications
3
31
0
2
Order By: Relevance
“…These risks persisted when controlled for potential cofounders. Caughey et al 11 reported that the incidence of emergency cesarean section also increased beyond 39 weeks of gestation, odds ratio 1.8, 2 and 2.1 for 40, 41 and 42 to 44 weeks, respectively, as compared with 39 weeks pregnancies. These findings warrant attention and indicate that these pregnancies need to be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risks persisted when controlled for potential cofounders. Caughey et al 11 reported that the incidence of emergency cesarean section also increased beyond 39 weeks of gestation, odds ratio 1.8, 2 and 2.1 for 40, 41 and 42 to 44 weeks, respectively, as compared with 39 weeks pregnancies. These findings warrant attention and indicate that these pregnancies need to be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the odds of chorioamnionitis were 1.4, 2 and 2.8 higher for pregnancies 40, 41 and 42 to 44 weeks, respectively, as compared with 39 weeks' pregnancies. Caughey et al, 11 in a study that included more than 100, 000 pregnant women, reported that the rate of chorioamnionitis also increased beyond 39 weeks' gestation (odds ratio when comparing to 39 weeks gestation, 1.3 and 1.7, for 40 and 42 to 44 weeks' gestation, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…(p<0.001), and rates of postpartum hemorrhage, endometritis and primary caesarean delivery increased at 41 weeks of gestation. 27 It has been traditionally accepted that complications are at their minimum in term pregnancies i.e. from 37-40 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal risks are asphyxia, aspiration, admission to intensive care after birth, bone fracture, peripheral nerve paralysis and others. 2,[3][4][5] It has been shown that maternal complications of pregnancy could increase after 40 weeks' gestation in low-risk women, especially nullipara. 6 In low-risk pregnancy at term, it has been suggested that active management of risk through the use of preventive labour induction prior to possible development of uteroplacental insufficiency or cephalo-pelvic disproportion can improve birth outcomes and reduce caesarean section rates.…”
Section: Introductionmentioning
confidence: 99%
“…2,[3][4][5] It has been shown that maternal complications of pregnancy could increase after 40 weeks' gestation in low-risk women, especially nullipara. 6 In low-risk pregnancy at term, it has been suggested that active management of risk through the use of preventive labour induction prior to possible development of uteroplacental insufficiency or cephalo-pelvic disproportion can improve birth outcomes and reduce caesarean section rates. 7,8 Since women in Asia and Africa have been shown to have a shorter duration of pregnancy compared with European women the authors of this appraisal recommend that clinicians in those regions should regard recommendation No.…”
Section: Introductionmentioning
confidence: 99%